Extensive expansion of the chemical diversity of fusidane-type antibiotics using a stochastic combinational strategy - Xiaojun Song; Jianming Lv; Zhiqin Cao; Huiyun Huang; Guodong Chen; Takayoshi Awakawa; Dan Hu; Hao Gao; Ikuro Abe; Xinsheng Yao (Elsevier, 2021)
Fusidane-type antibiotics, represented by helvolic acid, fusidic acid and cephalosporin P1, are fungi-derived antimicrobials with little cross-resistance to commonly used antibiotics. Generation of new fusidane-type derivatives is therefore of great value, but this is hindered by available approaches. Here, we developed a stochastic combinational strategy by random assembly of all the post-tailoring genes derived from helvolic acid, fusidic acid, and cephalosporin P1 biosynthetic pathways in a strain that produces their common intermediate. Among a total of 27 gene combinations, 24 combinations produce expected products and afford 58 fusidane-type analogues, of which 54 are new compounds. Moreover, random gene combination can induce unexpected activity of some post-tailoring enzymes, leading to a further increase in chemical diversity. These newly generated derivatives provide new insights into the structure‒activity relationship of fusidane-type antibiotics. The stochastic combinational strategy established in this study proves to be a powerful approach for expanding structural diversity of natural products.